2011
DOI: 10.1371/journal.pone.0023882
|View full text |Cite
|
Sign up to set email alerts
|

Matrin 3 Binds and Stabilizes mRNA

Abstract: Matrin 3 (MATR3) is a highly conserved, inner nuclear matrix protein with two zinc finger domains and two RNA recognition motifs (RRM), whose function is largely unknown. Recently we found MATR3 to be phosphorylated by the protein kinase ATM, which activates the cellular response to double strand breaks in the DNA. Here, we show that MATR3 interacts in an RNA-dependent manner with several proteins with established roles in RNA processing, and maintains its interaction with RNA via its RRM2 domain. Deep sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
152
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 38 publications
7
152
1
Order By: Relevance
“…1; Johnson et al 2014). Matrin-3 is a DNA-and RNA-binding protein with a role in promoting mRNA stability (Salton et al 2011) and has also been suggested to associate with TDP-43 (Ling et al 2010), although the interaction was shown to be RNA-dependent (Johnson et al 2014). While the precise nature of Matrin-3 in cellular granules with other disease-related proteins in unclear, such findings reinforce the convergence of different ALS genes in the same physical processes.…”
Section: Rbps and Membraneless Organellesmentioning
confidence: 96%
“…1; Johnson et al 2014). Matrin-3 is a DNA-and RNA-binding protein with a role in promoting mRNA stability (Salton et al 2011) and has also been suggested to associate with TDP-43 (Ling et al 2010), although the interaction was shown to be RNA-dependent (Johnson et al 2014). While the precise nature of Matrin-3 in cellular granules with other disease-related proteins in unclear, such findings reinforce the convergence of different ALS genes in the same physical processes.…”
Section: Rbps and Membraneless Organellesmentioning
confidence: 96%
“…Of note, some of these proteins are very abundant in normal breast tissue, such as MATR3 (Matrin-3), CPSF7 (Cleavage and Polyadenylation Specificity Factor Subunit 7), DX39B (Spliceosome RNA Helicase DDX39B), and HDAC1 (Histone Deacetylase 1), and all were down-regulated during EMT and also in the aggressive phenotype of MDA-MB-231. MATR3 plays a role in transcription, may interact with other nuclear matrix proteins, and binds to mRNA (43). CPFS7 is a component of the cleavage factor Im complex that plays a key role in pre-mRNA 3Ј-processing, binds to cleavage and polyadenylation RNA substrates, and is a target of miR-26b, which is a potent regulator of cancer behavior in estrogen receptor-positive cancers (44).…”
Section: Validation Of Proteomic Findings Using Antibody-basedmentioning
confidence: 99%
“…One new finding is that TF silencing profoundly down-regulated the expression of matrin 3, a 407 highly conserved inner nuclear matrix protein which, through a direct interaction with hnRNP 408 proteins and with the DNA and RNA helicase DHX9, might control RNA metabolism and 409 stabilisation [50]. 410…”
Section: Discussion 375mentioning
confidence: 99%